Civic Education and Global Citizenship: A Deweyan Perspective - Chikwe, Moses (In Factis Pax: Journal of Peace Education and Social Justice, 2012)
The idea of citizenship, according to the “The Penguin Dictionary of Sociology”, can be traced back to the classical period of Greece and Rome through the renaissance. In modern times citizenship is the product of revolutions, especially the French Revolution. “Citizenship is a politico-juridical status that confers an identity, and determines the distribution of resources within society”. It involves some notion of contribution to the common good of the nation state. Webster’s dictionary defines citizenship as “the state of being vested with the rights, privileges, and duties of a citizen”. Whereas it refers to a citizen as one who inhabits a city and is entitled to its privileges or franchises. Lacking in these definitions of citizenship is the interesting conceptualization and understanding of citizenship in the global and multicultural context. This lack is also evident in the current understanding of civic education, which is framed around the formation of the democratic ideals and values of a particular nation state in the individual members of the society. Nevertheless, civic education does hold the promise of expanding the narrow goal of traditional citizenship to the global perspective, due to the organized capacity of civic education and schooling in general in communicating the civic ideals.